Say No to Licensing: It Is Both Impractical and Immoral. Issue 2 (29th June 2017) - Locke, Edwin A.
Abstract : I have written on this subject in the past (Locke, 2009 ; Locke, Mode, & Binswanger, 1980 ), but here I will both reiterate and expand on what I have said before.